ANALISIS HUKUM PERJANJIAN TERHADAP PRAKTIK PINJAM MEMINJAM DI PASAR WAMANGGU MERAUKE - Philipus Bone; Yuldiana Zesa Azis; Herry Hendri Fernando Mote (Animha Law Journal, 2025)
An agreement is an agreement, either written or verbal, made by two or more parties who agree to comply with the terms stated in the agreement. One of the economic phenomena that often occurs in the context of traditional markets is the practice of borrowing and lending between business actors, which is carried out to meet capital needs, both in the short and long term. This practice is commonly found in Wamanggu Market, Merauke, which is the main market and center of economic activity for the local community. This study aims to analyze the suitability of borrowing and lending practices in Wamanggu Market with the provisions of the law of agreements as stated in the BW, especially those related to borrowing and lending agreements, as well as the validity and form of the agreement. This type of research is empirical juridical, namely research with legal research on applicable laws and regulations and the actual reality in society. The results of the study show that most of the lending and borrowing practices in Wamanggu Market are carried out verbally without being stated in written form. This has implications for minimal legal certainty and increased risk of default. Even in some cases, practices were found that have the potential to violate the law, namely unlawful acts that cause losses to other parties. For example, setting high interest rates without a transparent and fair agreement and imposing hidden fines that were not agreed upon in advance. Therefore, this study recommends the importance of legal education for business actors in the market, strengthening regulations on informal lending and borrowing practices and encouraging them to make agreements in written form. This is intended to create a lending and borrowing system that is fairer, more transparent, and provides adequate legal protection for all parties involved.